2023
DOI: 10.1007/s10557-023-07477-6
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance Triggers Atherosclerosis: Caveolin 1 Cooperates with PKCzeta to Block Insulin Signaling in Vascular Endothelial Cells

Abstract: Objective To date, therapies for endothelial dysfunction have primarily focused on ameliorating identified atherosclerosis (AS) risk factors rather than explicitly addressing endothelium-based mechanism. An in-depth exploration of the pathological mechanisms of endothelial injury was performed herein. Methods Aortic caveolin 1 (Cav1) knockdown was achieved in mice using lentivirus, and AS was induced using a high-fat diet. Mouse body weight, blood glucose,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Arterial stiffness is considered an independent risk predictor of cardiovascular events ( 38 ). IR can damage the endothelium of blood vessels and lead to inflammatory reactions, which may easily lead to arterial stiffness and arteriosclerosis ( 39 ). A Meta-analysis of 37,780 Individuals showed that IR is closely related to arterial stiffness ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Arterial stiffness is considered an independent risk predictor of cardiovascular events ( 38 ). IR can damage the endothelium of blood vessels and lead to inflammatory reactions, which may easily lead to arterial stiffness and arteriosclerosis ( 39 ). A Meta-analysis of 37,780 Individuals showed that IR is closely related to arterial stiffness ( 40 ).…”
Section: Discussionmentioning
confidence: 99%